Digital matrix of the Russian economy - I. V. Groshev; S. V. Koblov (Управление)
The article analyses the problems of digitalisation, which has become dominant in recent years, which is justified by numerous data on scientific publications, the number of patents, the volume of investments and publications in various media. The article is based on the methodology of an integrated approach and system analysis. The theoretical basis of the article was the publications of Russian researchers devoted to the problems of the Russian economy҅s digitalisation. Familiarisation with regulatory documents and government programmes, methods of comparative analysis were chosen as research methods. The methods used also included the method of expert assessments, normative and logical methods. The analysis of methods, mechanisms, tools and other aspects of updating the track of digital transformation of the Russian economy is carried out. Based on and summarizing the results of the study, nine directions for the development of end-to-end technologies have been formulated and a block diagram of the model of the government programme «Digital Economy» is presented. Separately, the culture of organisations is considered, which is a barrier to the digital transformation of companies, which evolves into a «digital culture». In conclusion, a modern rating of end-to-end trends of the digitalisation process is presented, and global end-to-end trends of digitalisation in the sectoral context demonstrating the track of development of the digital matrix of the Russian economy. The presented information will allow to navigate in the established directions of development of end-to-end technologies of the Russian economy, and to make rational management decisions to representatives of Russian business and top management of Russian companies.